In Peri-Urban Areas... Protected cultivation of vegetables is remunerative - Prabhakar, M; Hebbar, S S; Nair, A K; Balakrishna, B (Indian Horticulture, 2019)
Protected or greenhouse cultivation of vegetables is gaining popularity because of high productivity of quality produce round the year with enhanced inputuse efficiency of water, nutrients, plant protection chemicals and manpower. As agriculture has a major share in the Indian economy and if India has to emerge as an economic power in the world, the increased productivity and farm income are very essential. Research on protected vegetable production started in 2000 at IIHR, Bengaluru, which resulted in the development of many technologies and made possible to realize high yield levels with superior produce quality in tomato, capsicum, cucumber and melons. In tomato and capsicum, yields have touched 300 and 200 tonnes per hectare per year and those of cucurbits 80-100 tonnes per hectare per crop.